Quality through engineering design - Kuo, Way (Amsterdam: Elsevier, 1993)
Addresses the issues of quality and engineering design in a formal way. Its aim is to foster the understanding and collaboration among scientists and engineers in the fields of conceptual approaches to engineering design, computational approaches in design, statistical design and analysis, reliability and quality control. engineering design in the context of quality, presenting views and sharing concepts. In addition to the quantitative models presented in this book, applications, strategic considerations and validated managerial practices are also considered. It illustrates the great value of developing communication channels between engineers and statisticians and between academic theoreticians and industrial practitioners, and of differentiating future design needs from the current design practice. It presents problems and solutions across the boundaries of nations and cultures. It is this particular quality that is essential to expanding world economic and enhancing human living standards. in engineering design. They should benefit from the modern statistical techniques and tutorials presented in the book and from the numerous reviews of successful, real applications of quality and reliability techniques to various design projects.
Conceptual and methodological design -- Management through strategic considerations of design -- Robust design design and data analysis -- Statistical approach and reliability -- Tolerances and discrete parts design -- Finite-element method for design -- Computing in design -- Materials processing and metrological design
Includes bibliography and index
Keywords: Statistics; Statistical quality control & related topics; Quality Control; Engineering